Dampak Akses dan Infrastruktur, Penggunaan, dan Keahlian Teknologi Informasi dan Komunikasi terhadap Konsumsi Telekomunikasi Rumah Tangga - Priambodo, Aji (Fakultas Ekonomi Universitas Kadiri, 2023)
This study aims to determine the effect of access and infrastructure, use, and expertise of information and communication technology on the average household telecommunication consumption. By using the panel data regression analysis method and the selected model is the Fixed Effect Model (FEM), in this study it was found that access and information and communication technology infrastructure had a positive but not significant effect, the use of information and communication information technology had a positive and significant influence, and Information and communication technology expertise has a positive and significant impact on household telecommunication consumption in 34 provinces in Indonesia in the 2017-2021 period.